Costa Rica. Logros significativos 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Costa Rica during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as marketing, trade, organic agriculture, rural development, territorial development, innovation, technology, research, security. food, health and safety and competitiveness. Finally, work was done to support small and medium-sized companies, cooperation between the public and private sectors, resilience against climate change, and value chains for corn, beans, cassava, chili, beef, and rice.